Phylogeny of the Cyrtodactylus irregularis species complex (Squamata: Gekkonidae) from Vietnam with the description of two new species - Nguyen, Sang Ngoc; Le, Thanh-Ngan Thi; Tran, Thi Anh Dao; Orlov, Nikolai L.; Lathrop, Amy; Macculloch, Ross D.; Le, Thuy-Duong Thi; Jin, Jie-Qiong; Nguyen, Luan Thanh; Nguyen, Tao Thien; Hoang, Dat Duc; Che, Jing; et al. (Zootaxa, 2013)
The number of described species of bent-toed geckos of the Cyrtodactylus irregularis species complex in Vietnam has increased from one to eight in the last six years. We combined morphological and molecular analyses to explore phylogenetic relationships among all described species in the group. The phylogeny required the description of two new species, Cyrtodactylus phuocbinhensis sp. nov. and Cyrtodactylus taynguyenensis sp. nov. Further, the tree resolved two additional undescribed clades that may also be new species. The species C. bugiamapensis and C. ziegleri were found to require redefinition. Cyrtodactylus phuocbinhensis sp. nov. is characterized by a series of enlarged femoral scales separated from preanal scales while Cyrtodactylus taynguyenensis sp. nov. does not possess enlarged femoral scales. Both new species are distinguished from other congeners by a combination of the following characters: small subcaudal scales, not transversely enlarged; presence (C. phuocbinhensis sp. nov.) or absence (C. taynguyenensis sp. nov.) of enlarged femoral scales; number of preanal pores; and dorsal pattern. Genetic distances between described species and new species were 16.5% and 2.0% in COI and RPL35, respectively, for C. phuocbinhensis sp. nov., and these distances were 18.8% and 2.2% for C. taynguyenensis sp. nov., respectively.